Analysis of Constitutional Court Decision Number 2/PHPU.PRES-XXII/2024 Concerning the Dispute over the Results of the 2024 Presidential Election from the Perspective of Siyasah Qadhaiyyah - Sani, Muhammad; Khalid, Khalid (IHSA Institute, 2025)
This study aims to analyze the Constitutional Court Decision Number 2/PHPU.PRES-XXII/2024 concerning the presidential election dispute in 2024 from the perspective of siyasah qadhaiyyah. The findings reveal that the Constitutional Court assessed the case solely from a legal-formal standpoint, emphasizing administrative and procedural evidence without considering the ethical dimensions of power and the socio-political impact of state resource abuse. In the siyasah qadhaiyyah framework, justice is not limited to procedural compliance but must be substantive and directed at preventing tyranny in governance. Judges, according to this perspective, are morally obliged to uncover the hidden motives of power behind legal formalities and to uphold public welfare (maslahah 'ammah). This research recommends a paradigm reform of the Constitutional Court, urging the Court to transcend legal positivism and uphold substantive justice aimed at protecting citizens' rights and the integrity of electoral processes. Thus, siyasah qadhaiyyah serves as an ethical and philosophical foundation for enhancing the Constitutional Court's role as the guardian of democratic justice, rather than merely functioning as a procedural interpreter of legal texts